2015
DOI: 10.3928/00485713-20150803-09
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Pharmacotherapy for Borderline Personality Disorder: A Review of the Available Randomized Controlled Trials

Abstract: Although there are no medications approved by the US Food and Drug Administration for the treatment of borderline personality disorder (BPD), polypharmacy is commonly encountered in individuals with BPD. This review summarizes the results of randomized controlled trials on the efficacy of pharmacologic agents in BPD. Pharmacotherapy in BPD is an adjunctive treatment aimed at stabilizing symptoms and behavior in a crisis situation, and it should be avoided whenever possible. Further studies are needed, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The treatment for PDs is primarily psychotherapy, with pharmacotherapy typically reserved as an adjunct to target specific symptoms (Francois et al, 2015; Rosowsky et al, 2018). A study of expert consensus indicated that personality-changing, adaptation-focused, and supportive-structuring treatment approaches are useful overall in geriatric psychiatry (Rosowsky et al, 2018).…”
Section: Treatmentmentioning
confidence: 99%
“…The treatment for PDs is primarily psychotherapy, with pharmacotherapy typically reserved as an adjunct to target specific symptoms (Francois et al, 2015; Rosowsky et al, 2018). A study of expert consensus indicated that personality-changing, adaptation-focused, and supportive-structuring treatment approaches are useful overall in geriatric psychiatry (Rosowsky et al, 2018).…”
Section: Treatmentmentioning
confidence: 99%
“…Recommendations for the treatment of borderline PD by antidepressants are limited by the situation that pharmacotherapeutic trials, mainly with SSRIs, were only carried out in small groups of patients or in non-blinded conditions. This explains why some review papers concluded that there is no clear-cut effect of antidepressants on the score of depression and on the general level of functioning, while small or even moderate effects were observed on anxiety, anger, separation anxiety, chronic dysphoria as well as boredom and emptiness (Hancock-Johnson et al 2017;Francois et al 2015). On the other hand, effects were only slight or moderate on other affective symptoms reported by borderline PD patients.…”
Section: Antidepressantsmentioning
confidence: 99%
“…For example, there is a growing literature examining biological factors associated with BPD but the translation to validated medical or psychopharmacological approaches has been slow 103105 . To date, there are no medications approved specifically for use in BPD, and intensive psychotherapy (usually lasting 12 months or more) is the treatment of choice for affected individuals 106, 107 . Such interventions are expensive and time intensive and do not reduce all BPD symptoms for all affected individuals.…”
Section: Summary and Future Directionsmentioning
confidence: 99%